Le BIT, la mesure du “travail des enfants” et la question de la scolarisation - Bernard Schlemmer (Cahiers de la Recherche sur l'Education et les Savoirs)
The paradigm of schooling for all is so strong that children out of school are simply considered as a marginal population that needs to be re-integrated into the norm. But in fact, the institution can function only by eliminating progressively those for whom the schooling system is too constraining, e.g. working children, since it is made almost impossible to simultaneously work and study. By praising the mere abolition of work for children, the ILO is obliged to give a definition of this problem – namely that child labour is harmful for children – that hides its real magnitude. By giving a priority to the protection of children instead of defending status of children as workers, the ILO is missing its mission. This position has gathered a large consensus from which the working children themselves are exchaded.